The good, the bad and the ugly - Alexandrino da Silva, A. (ESS Data Visualisation Workshop, 2019)
https://ec.europa.eu/eurostat/cros/system/files/2_ana_alexandrino_silva.pdf Examples of the dos and don'ts of commons data visualizations. The “good” applies to charts that we consider interesting and could be reproduced elsewhere. The “bad” applies to data visualizations that could be improved using different types of charts. The “ugly” is a chart, misleads the reader, and is really an evil choice.